Philosophical foundations of the law of unjust enrichment - Chambers, Robert, 1957-; Mitchell, Charles (Charles Christopher James); Penner, J. E. (James E.) (Oxford : Oxford University Press, 2009)
This volume takes stock of the rapid changes to the law of unjust enrichment over the last decade. It offers original contributions from leading private law theorists examining the philosophical foundations of the law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Unjust enrichment; Law -- Philosophy